An Introduction to Molecular Biotechnology - Wink, Michael;Ed (Wiley-Blackwell, 2011)
Life sciences have advanced at a rapid speed. The information of cell and molecular biology as well as genetics can be applied to biotechnology and medicine. This new field has been termed "Molecular Biotechnology" and its focus is more on Science and its techniques than on fermenters and engineering. This book summarizes the basic knowledge of cell and molecular biology, introduces the main methods and explains concepts and applications in more detail. A very detailed introduction to the fundamentals in molecular and cell biology is followed by an overview of standard techniques applied in molecular biotechnology -- including chromatography and electrophoresis, cloning techniques, gene expression systems, immunological methods, labeling of proteins and in situ-techniques, microscopy and laser systems. The third part then focuses on the key topics of molecular biotechnology, ranging from functional genomics, proteomics and bioinformatics to drug targeting, recombinant antibodies, structural biology, gene therapy and knock mice. The whole is rounded off by a section on biotechnology in industry dealing with patenting issues, company foundation and market opportunities. Biotechnology is our use of living organisms to produce useful products and services. This involves the manipulation of living organisms, frequently through genetic engineering. For years now there have been products on the market produced with the help of biotechnology, for example beer and yoghurt. Today, more and more products derived from biotechnology are being brought onto the market. Medicines such as insulin for the treatment of diabetes have been used for years, while others have only recently been introduced. Over 600 pages this book provides students and professionals in life sciences, pharmacy and biochemistry with all they need to know about molecular biotechnology.